How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10694591 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1014 ZenodoArchiveConcept: 10694590
Keywords: _r:AddedByMyEducationEvidence

Rapport d’Observation du Testing Alpha - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo; Koomar, Saalim (EdTech Hub, 2025)
This document, details the Alpha user testing of a digital learning platform and educational applications for the Ministry of National Education of Madagascar, aimed at training 2000 teachers. Conducted in July 2024, the testing focused on functionality and accessibility. Twenty-nine testers, primarily web developers and instructional designers, used a Google Forms questionnaire to evaluate the platform and applications. The results showed that while the platform was generally functional, with most features validated, several areas needed adjustments, particularly in accessibility and specific functions like the quiz timer. The applications had more issues, with several features requiring fixes and accessibility being a significant concern. Key recommendations included diagnosing and fixing defective parts, restructuring modules for better accessibility, optimising multimedia file sizes, and creating a detailed user guide. The testing highlighted the need for improvements before the Beta testing phase with teachers. Keywords: teacher professional development; Madagascar; Moodle; user testing Ce document détaille les tests utilisateurs en phase Alpha d’une plateforme d’apprentissage numérique et d’applications éducatives développées pour le Ministère de l’Éducation Nationale de Madagascar, dans le cadre de la formation de 2 000 enseignants. Réalisés en juillet 2024, ces tests ont porté sur la fonctionnalité et l’accessibilité. Vingt-neuf testeurs, principalement des développeurs web et des concepteurs pédagogiques, ont évalué la plateforme et les applications via un questionnaire Google Forms. Les résultats ont montré que, bien que la plateforme soit globalement fonctionnelle avec la plupart des fonctionnalités validées, plusieurs ajustements étaient nécessaires, notamment en matière d’accessibilité et pour certaines fonctions spécifiques comme le minuteur des quiz. Les applications présentaient davantage de problèmes, plusieurs fonctionnalités nécessitant des corrections et l’accessibilité étant un défi majeur. Les principales recommandations incluaient le diagnostic et la correction des éléments défectueux, la restructuration des modules pour une meilleure accessibilité, l’optimisation de la taille des fichiers multimédias et la création d’un guide utilisateur détaillé. Ces tests ont mis en évidence la nécessité d’améliorations avant la phase de test Beta avec les enseignants. Mots clés: formation pédagogique; Madagascar; Moodle; test utilisateur An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230731 ZenodoArchiveConcept: 14230730 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1035 10.53832/edtechhub.1071
Keywords: _r:AddedByMyEducationEvidence

Guide pour les administrateurs de la plateforme Formation À Distance - Rasolohery, Hasiniavo; Ranaivosamoelina, Tokiniaina (EdTech Hub, 2025)
This is a practical guide for administrators of the Formation À Distance (FAD) platform in Madagascar. The guide provides instructions on managing the platform, with a focus on evaluations and forums. It covers topics such as setting up different types of evaluations (quizzes, assignments), configuring forum settings, managing discussions, and moderating forums. It also includes best practices for both evaluations and forums, as well as security considerations. The document provides step-by-step instructions with screenshots for specific tasks like activating edit mode, adding activities or resources, setting up tests, and configuring forum parameters. It also includes a glossary of terms, references, and useful links. The guide is intended to help administrators effectively manage the FAD platform and support teachers and students in their online learning activities. Keywords: teacher professional development; Madagascar; Moodle; tablet; administrator guide Ceci est un guide pratique destiné aux administrateurs de la plateforme de Formation À Distance (FAD) à Madagascar. Il fournit des instructions pour la gestion de la plateforme, en mettant l’accent sur les évaluations et les forums. Il couvre des sujets tels que la configuration des différents types d’évaluations (quiz, devoirs), le paramétrage des forums, la gestion des discussions et la modération des forums. Il inclut également les meilleures pratiques pour les évaluations et les forums, ainsi que des considérations de sécurité. Le document propose des instructions détaillées, illustrées par des captures d’écran, pour des tâches spécifiques comme l’activation du mode édition, l’ajout d’activités ou de ressources, la mise en place de tests et le paramétrage des forums. Il comprend également un glossaire des termes, des références et des liens utiles. Ce guide vise à aider les administrateurs à gérer efficacement la plateforme FAD et à soutenir les enseignants et les élèves dans leurs activités d’apprentissage en ligne. Mots clés: formation pédagogique; Madagascar; Moodle; tablette; guide pour les administrateurs An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230806 ZenodoArchiveConcept: 14230805 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1062 10.53832/edtechhub.1074
Keywords: _r:AddedByMyEducationEvidence

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13256782 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1053 ZenodoArchiveConcept: 13256781
Keywords: _r:AddedByMyEducationEvidence

Leveraging Existing Technology in Low-Resource Settings to Support Learning: Conceiving and developing implementation plans for schools - Hayat, Amal; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
This document serves as a practical guide for implementers and decision-makers on how available technologies can effectively support teaching and learning in schools worldwide. Drawing on existing evidence of successful EdTech interventions in low-resource settings, particularly within Southeast Asia, it offers guidance on the essential steps in the early phases of EdTech implementation. The report also provides recommendations for transitioning from the initial conception phase to developing a comprehensive implementation plan. Keywords: EdTech implementation guide; low-resource settings; ASEAN; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14727493 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1088 ZenodoArchiveConcept: 14727492
Keywords: _r:AddedByMyEducationEvidence

AI in the Classroom: A rapid evaluation of AI-generated lesson plans in Islamabad’s public schools - Aslam, Nawaz; Qureshi, Ghada; Hassan, Syed Mustafa (EdTech Hub, 2025)
This report presents a rapid evaluation of AI-generated lesson plans currently being used in public schools in rural and urban Islamabad under the National Institute of Excellence in Teacher Education (NIETE). These centrally developed, scripted lesson plans are aligned with the national curriculum and built on the Gradual Release of Responsibility (GRR) model, with additional elements of the 5E and Inquiry-Based Learning (IBL) models in science, and the Concrete-Pictorial-Abstract (CPA) model in maths. Using a mixed-methods approach—including teacher surveys, focus group discussions, key informant interviews, and an expert rubric-based review—the study assesses the lesson plans' quality, relevance, and adaptability. Teachers expressed strong support for the lesson plans, especially in terms of reduced workload and structured delivery, though concerns were raised around flexibility, contextual responsiveness, and teacher agency. While the study does not evaluate student learning outcomes, it provides actionable insights and recommendations for improving the design, support, and implementation of AI-generated instructional tools, particularly as the programme scales to other provinces in Pakistan, such as Balochistan. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15077892 ZenodoArchiveConcept: 15077891 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1104 10.53832/edtechhub.1105 10.53832/edtechhub.1107 10.53832/edtechhub.1108 2405685:FR4GREKJ 2405685:XG7G3FDM
Keywords: _r:AddedByMyEducationEvidence

Artificial Intelligence and Education Systems in 2035: Fourteen trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in artificial intelligence (AI) that might occur over the next 10 years. It begins by capturing fourteen trends, relating to AI that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15792725 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1125 ZenodoArchiveConcept: 15792724
Keywords: _r:AddedByMyEducationEvidence

Note de conseils sur la plateforme numérique - Messa, Angele; Koomar, Saalim; Mitchell, Joel (EdTech Hub, 2025)
This document is a guidance note on digital platforms, specifically focusing on e-learning and the use of Opale and Moodle software. It aims to support the implementation of a digital learning platform in Madagascar. The report addresses questions and challenges faced by the Ministry of National Education in developing and deploying digital educational content. It covers various aspects of e-learning, including evaluation methods, content structuring, accessibility, interactivity, and technical requirements. Key topics include different evaluation models, types of e-learning evaluation (formative and summative), guidelines for using Opale, tablet specifications for online learning, ensuring course accessibility, and using Moodle both online and offline. The document also provides a checklist for ensuring quality in e-learning course development and implementation. Keywords: e-learning; Moodle; Opale; digital platform; accessibility; usability; Madagascar Ce document est une note d’orientation sur les plateformes numériques, avec un accent particulier sur l’e-learning et l’utilisation des logiciels Opale et Moodle. Il vise à soutenir la mise en place d’une plateforme d’apprentissage numérique à Madagascar. Le rapport aborde les questions et défis rencontrés par le Ministère de l’Éducation Nationale dans le développement et le déploiement de contenus éducatifs numériques. Il traite de divers aspects de l’e-learning, notamment les méthodes d’évaluation, la structuration des contenus, l’accessibilité, l’interactivité et les exigences techniques. Les principaux sujets incluent les différents modèles d’évaluation, les types d’évaluation en e-learning (formative et sommative), les recommandations pour l’utilisation d’Opale, les spécifications des tablettes pour l’apprentissage en ligne, l’accessibilité des cours et l’utilisation de Moodle en mode en ligne et hors ligne. Le document propose également une liste de contrôle pour garantir la qualité du développement et de la mise en œuvre des cours en e-learning. Mots clés: e-learning; Moodle; Opale; platforme numériques; accessibilité; usabilité; Madagascar An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14995952 ZenodoArchiveConcept: 14995951 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7303773 10.53832/edtechhub.1101 2405685:RMJK6G6Q
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15366685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1113 ZenodoArchiveConcept: 15366684
Keywords: _r:AddedByMyEducationEvidence